Guidance on how to balance the purchasing environment and processes to save resources - a validity examination of a holistic model - Maria M. Wittinger; Krisztina Demeter (Cogent Business & Management, 2024)
Despite the evolution of purchasing operations over many years, a comprehensive perspective is lacking in practice, leading to inefficiencies. This study aims to validate a model designed to guide how to balance the purchasing environment. It comprehensively delineates the general pattern (a map) of real-life purchasing procedures and standardizes these elements to provide clarity and coherence. The model's novelty lies in the thoughtful selection and arrangement of factors, and their classification into two groups forces and drivers. This facilitates a structured approach to analyzing purchasing status through a checklist. By mapping purchasing activities, the model connects issues to its factors. After identifying existing weaknesses in operations by this linkage among the model's elements and problems, the framework serves as a valuable diagnostic tool supporting managerial decisions and enhancing efficiency. The validation study comprised case studies and survey research conducted at five multinational companies, involving over 130 purchasing professionals. Research proved the model's validity in terms of correctness, completeness, and applicability.
Keywords: 650; Cross-functional integration; it solutions; procurement; purchasing; strategies; supplier management